Use of Beta-Carotene Pigment to Improve Food Product Chemical and Sensory Qualities: A Review - Suryana, Muhammad Rifqi; Haziman, Muhammad Luthfan; Islamawan, Praboyo Ardin; Hari Hariadi; Dandy Yusuf (Journal Akademik Universitas Swiss German, 2023)
Beta-carotene is a pigment that occurs widely and abundantly in nature. Beta-carotene can be found in some fruits and vegetables. Commonly, beta-carotene consistently bonds to other carotenoid compounds. Beta-carotene is a powerful colorant with beneficial effects on human health due to its ability to radical scavenging. Beta-carotene is obtained through the process of extraction with suitable solvent. The extraction method influenced the profile and quality of beta-carotene. The sonochemical approach using ultrasound, microwaves, and ohmic heating is eco-friendly and helps decrease the amount of solvent used, reduce the extraction time, increase the yield of beta-carotene from the sources, and increase the efficiency of the food applied. It is easier for consumers to accept natural dyes with high stability and efficiency. The present review describes detailed information about the quality of beta-carotene extract, isolation methods, and factors that affect the efficiency of natural food colorants applied to food products, which is helpful for the further development of food product formulations.